Implementation Of Cooperative Learning Method In Aqidah Akhlak Subject At SMA IT Jabal Noor - Marista, Refi; Tumiran, Tumiran (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to analyze the implementation of the Cooperative Learning method in the subject of Aqidah Akhlak at SMA IT Jabal Noor and its impact on improving students' understanding and character. The Cooperative Learning method was chosen for its ability to encourage student interaction, increase engagement, and deepen material comprehension through group collaboration. This research employs a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The research findings indicate that the implementation of the Cooperative Learning method in the Aqidah Akhlak subject is carried out through several steps, namely forming heterogeneous groups, assigning material discussions, group presentations, and learning reflections. The use of this method has been proven to increase students' active participation, strengthen relationships among students, and facilitate understanding of the moral values being taught. However, there are several challenges, such as differences in students' levels of understanding and time management in group activities. The conclusion of this study suggests that teachers should be more creative in designing Cooperative Learning-based teaching strategies and provide intensive guidance to ensure all students can contribute optimally. Thus, the implementation of this method can bring greater positive impacts on teaching Aqidah Akhlak at SMA IT Jabal Noor.